Analisis Implementasi PPh Pasal 4 Ayat (2) dan Implikasinya terhadap Manajemen Keuangan pada PT. Ciputra Development Tbk Tahun 2024 - Ainun Niswati; Rudi Sanjaya; Rindi Kartika; Jefin Kristenson (Pajak dan Manajemen Keuangan, 2026)
This study aims to analyze the implementation of Income Tax (PPh) Article 4 Paragraph (2) and its implications for financial management at PT Ciputra Development Tbk (CTRA) in 2024. The study used a qualitative approach using documentation study techniques on the company's consolidated financial statements and relevant tax regulations. The results indicate that the Final Income Tax burden of IDR 311.89 billion significantly impacted the company's cost structure and cash flow. Differences in Final Income Tax rates in the real estate, property rental, and construction services business segments require accurate income classification and integrated tax administration management. The implementation of the Unified e-Bupot system has been proven to improve tax administration efficiency and minimize the risk of data discrepancies with the Directorate General of Taxes. In addition, the company implemented a tax dispute mitigation strategy by strengthening documentation and legal approaches. This study implies that the integration of tax management, information technology, and good corporate governance is a critical factor in maintaining tax compliance and the stability of the financial performance of property companies.